RESIDUAL EFFECTS OF COVER CROPS AND SOIL AMENDMENTS ON CARBON CONTENT AND STOCK IN A DEGRADED SOIL - Carolina dos S. B. Bonini; Jorge J. Delfim; Josiane Lourencetti; Laura S. Nantes; Melissa A. Santos; José A. L. Souza (Engenharia Agrícola)
ABSTRACT Cover crops have proven effective in restoring ecosystem services in areas degraded by hydroelectric plant operations. This study evaluated the residual effects of cover crops and soil amendments on soil organic carbon (SOC) content and soil organic carbon stock (SOCS) in a degraded Oxisol. The experiment was established in 1992 in a randomized complete block design, with different cover crop species combined with lime and lime + gypsum applications. Soil samples were collected at 0–0.05, 0.05–0.10, and 0.10–0.20 m soil depths to analyze SOC content, SOC stock, pH, and bulk density. Results demonstrated that, nearly 30 years later, cover crops and soil amendments significantly influenced SOC—particularly at the 0.05–0.10 m and 0.10–0.20 m depths—with treatments T2 and T7 showing the greatest effects. SOC stock increased in treatments T2, T6, and T7 at 0.10–0.20 m depth. Overall, SOC content and stock were influenced using cover crops and lime application; however, these effects varied depending on the cover crop species, particularly in terms of carbon distribution throughout the soil profile.